LANGUAGE POLITENESS BASED ON THE PRINCIPLE OF STUDENT COOPERATION IN UNIVERSITY - Jafar, jafar (Universitas Cokroaminoto Palopo, 2024)
It aims to describe the defenseless behaviors of Indonesian language based on compliance and violation of the principle of cooperation in student discussion activities in the class of 2022 Education Indonesian of Pancasakti University Makassar. This type of research is qualitatively descriptive. The results showed that the scale of Indonesian manners based on the compliance of the principle of cooperation in the discussion activities of students in the class of 2022 Education Study Program Indonesian of Pancasakti University Makassar thanks to varying categories, namely: polite, fairly polite, and less polite with the compliance of four types of maxims; and not be well-mannered with the compliance of two types of maxims. Similarly, the scale of Indonesian-language manners based on violations of the principle of cooperation in student discussion activities in the class of 2022 education programs Indonesian Pancasakti University makassar thanks to the varied category, namely: sufficient manners with violations of two types of maxims; less polite to the violation of three types of maxims; and not well mannered with violations of four types of maxims.